Transoceanic Dispersal and Plate Tectonics Shaped Global Cockroach Distributions: Evidence from Mitochondrial Phylogenomics. (6th February 2018) - Bourguignon, Thomas; Tang, Qian; Ho, Simon Y W; Juna, Frantisek; Wang, Zongqing; Arab, Daej A; Cameron, Stephen L; Walker, James; Rentz, David; Evans, Theodore A; Lo, Nathan
Abstract: Following the acceptance of plate tectonics theory in the latter half of the 20th century, vicariance became the dominant explanation for the distributions of many plant and animal groups. In recent years, however, molecular-clock analyses have challenged a number of well-accepted hypotheses of vicariance. As a widespread group of insects with a fossil record dating back 300 My, cockroaches provide an ideal model for testing hypotheses of vicariance through plate tectonics versus transoceanic dispersal. However, their evolutionary history remains poorly understood, in part due to unresolved relationships among the nine recognized families. Here, we present a phylogenetic estimate of all extant cockroach families, as well as a timescale for their evolution, based on the complete mitochondrial genomes of 119 cockroach species. Divergence dating analyses indicated that the last common ancestor of all extant cockroaches appeared ∼235 Ma, ∼95 My prior to the appearance of fossils that can be assigned to extant families, and before the breakup of Pangaea began. We reconstructed the geographic ranges of ancestral cockroaches and found tentative support for vicariance through plate tectonics within and between several major lineages. We also found evidence of transoceanic dispersal in lineages found across the Australian, Indo-Malayan, African, and Madagascan regions. Our analyses provide evidence that both vicariance and dispersal have played important roles in shaping the distribution and diversity of these insects.